Genetics of malocclusion: a review - Mokhtar@Makhtar, Khairani Idah; Abu Bakar, Noraini; Md Ali @ Tahir, Aisyah Hanani (Kulliyyah of Dentistry, International Islamic University Malaysia, 2020)
Malocclusion is one of the most common craniofacial problems observed worldwide. Affected individuals suffer not only from aesthetic concerns but also from functional problems, such as with mastication and pronunciation. The prevalence of malocclusion in East Asians is higher than in other races. Reports have shown besides environmental factors, there is association between certain types of malocclusion with specific genes. Positive association of mandibular prognathism has been implicated to genes such as Matrilin-1; while mutation in DUSP6 has also been shown to contribute to the incidence of malocclusion. This review aimed to briefly discuss the involvement of other additional genes such as MYO1H and PAX9 in the incidence of malocclusion as observed from our local institution.